DECONSTRUCTIVE HEGEMONY ON THE MARGINAL GENDER AND IDENTITY SEEN IN MAUGHAM’S “THE LOTUS EATER” AND HEAD’S “THE PRISONER WHO WORE GLASSES” - Turuk, Didimus Estanto (Lire Journal (Journal of Linguistics and Literature), 2019)
Hegemony is one of the Marxist applicative concepts employed during the European colonial period. The colonization constructed a power domination of the European countries toward the colonized. The constructed hegemony performed by the European colonizers is the center of discussion in this essay. This essay aims to examine the hegemony lies within the two short stories which are “The Lotus Eater” by W. Somerset Maugham and “The Prisoner Who Wore Glasses” by Bessie Head through Post-Colonial perspectives and accompanied by the gender perspectives. The constructed hegemony is the major theory of the analysis to scrutinize the oppressions both racial and gender base, however the further analysis is going to scrutinize the abrogation of the hegemony. On scrutinizing the hegemony, Derridian deconstruction is employed to construct the analysis on the abrogation of the European constructed hegemony. Keywords: Hegemony, Deconstruction, Post-colonial, Gender, Abrogation